Lung Neoplasm versus Diaphragmatic Hernia. A Case Report - Dayana Alomá Fortún; Iris Gonzalez Morales; María Caridad Fragoso Marchante (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
A case of an 82-year-old female patient admitted to the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos because of respiratory symptoms and general malaise is presented. Although she was already under treatment, prescribed in her health area, the symptoms had worsened. When a chest radiograph was performed, the probability of a pulmonary neoplasm was suspected. After several tests, it was concluded that the patient had a diaphragmatic hernia. This is a rare condition that, in adults, is diagnosed incidentally due to the lack of early symptoms. Therein lies the interest of this case; its presentation aims at describing and analyzing the clinical findings, as well as commenting them, after briefly reviewing the subject.